Cognitive science : an introduction to the study of mind - Friedenberg, Jay; Silverman, Gordon W.; Spivey, Michael (Michael James) (Thousand Oaks : SAGE Publications, Inc., 2022)
Cognitive Science provides a comprehensive and up-to-date introduction to the study of the mind. The authors examine the mind from the perspective of different fields, including philosophy, psychology, neuroscience, networks, evolution, emotional and social cognition, linguistics, artificial intelligence, robotics, and the new framework of embodied cognition. Each chapter focuses on a particular disciplinary approach and explores methodologies, theories, and empirical findings. Substantially updated with new and expanded content, the Fourth Edition reflects the latest research in this rapidly evolving field.
Core Textbook.
Includes bibliographical references.
Keywords: elektronické knihy; electronic books; Psychology -- Cognitive Psychology -- Philosophy